2001
DOI: 10.1128/jcm.39.11.4037-4041.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR for Simultaneous Identification of Staphylococcus aureus and Detection of Methicillin and Mupirocin Resistance

Abstract: In this work, we describe a multiplex PCR assay for the detection of clinically relevant antibiotic resistance genes harbored by some Staphylococcus aureus isolates and for the simultaneous identification of such isolates at the species level. Conditions were optimized for the simultaneous detection of the 310-, 456-, and 651-bp regions of the mecA (encoding high-level methicillin resistance), ileS-2 (encoding high-level mupirocin resistance), and femB (encoding a factor essential for methicillin resistance) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 28 publications
3
91
0
1
Order By: Relevance
“…This strain was isolated from raw human milk (LC2). Phenotypic and genotypic tests, identification of the nuc gene (Brakstad et al 1992), detection of the mecA gene (Perez-Hoth et al 2001), and chromosomal cassette typing mec (ssmec) (Boye et al 2007) were conducted to identify the strains. The isolated LC2 was positive for the nuc gene and mecA as well as ssmec, and thus typed as IV, which characterized it as a CA-MRSA strain.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…This strain was isolated from raw human milk (LC2). Phenotypic and genotypic tests, identification of the nuc gene (Brakstad et al 1992), detection of the mecA gene (Perez-Hoth et al 2001), and chromosomal cassette typing mec (ssmec) (Boye et al 2007) were conducted to identify the strains. The isolated LC2 was positive for the nuc gene and mecA as well as ssmec, and thus typed as IV, which characterized it as a CA-MRSA strain.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the high capacity of molecular methods such as Pulsed-field gel electrophoresis (PFGE), RT-PCR and PCR-based methods to increase the rapidity and accuracy of resistance testing [1,6,14,15,16,21,22].…”
Section: Discussion:-mentioning
confidence: 99%
“…These methods detect only phenotypic expression of methicillin resistance without the presence of the mecA gene [17]. Since phenotypic methods are not discriminating enough and are highly dependent on growth conditions, the use of genetic approach, such as DNA hybridization and PCR, is essential to stop the spread of S. aureus methicillin-resistant and to increase the rapidity and accuracy of their identification and their antibiotics resistance patterns [6].…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation
“…The mecA gene which encodes PBP2a is considered a useful molecular marker of putative methicillin resistance in S. aureus. S. aureus strains have a tendency to accumulate additional resistance determinants, resulting in the formation of multiple-antibiotic resistant MRSA strains which are creating therapeutic problems and limiting the choice of therapeutic options [12].…”
mentioning
confidence: 99%